An embedded system for the processing of ECG signals - Liu, Yiying. (2012)
This report documents the works the author has done during this Final Year Project period. As the first attempt in integrating ECG machine functions to an embedded system known as WinCE 5.0, a set of applications for use in WinCE 5.0 environment on ARM 9 platform is designed and developed from zero. This set of WinCE application covers the functions from ECG data acquisition, ECG signal processing and HRV analysis to HRV result communication using Bluetooth technology.